Research methodologies an Islamic perspective - Shah, Asadullah; Shah, Sayed Inayatullah; Shah, Abdul Salam (IIUM Press, 2016)
This book presents the most necessary aspects for conducting research including Islamic perspectives on research. It is very suitable for research beginners and as well as experienced researchers to conduct research. The content of this book start from simple research definitions, literature review and its important outcomes, research designs, methods and methodologies, scales of measures and analysis methods and presented in an easiest way to understand. The main aim of this book is to provide research students a comprehensive and complete view of research process and material to begin research with accurate and very precise understanding of the same.